Thermal advection analysis of cooling waves of Iran - Younes Khosravi; Mehdi Dostkamian; Allah Morad Taherian; Amin Shiri Karim vand (تحقیقات کاربردی علوم جغرافیایی)
Survey of advection of cold waves in Iran is the main aim of this study. In this regard, 45 synoptic stations were employed and studied. In order to investigate the thermal advection of cold waves, 1000, 850, 700 and 500 hp levels were reviewed and analyzed. Results indicated that cold waves in Iran most affected thermal advection caused by Tibet- Siberia, Siberias integrated Turkmenistan high-pressure, High pressure belt of Siberia - East Europe High pressure, Siberian high-pressure multi-core pattern and High-pressure belt of East of Caspian Sea integrated Black Sea High pressure. In the meantime, thermal advection of Siberian high pressure has been more impressive than other patterns. This system moved towards lower latitudes by anti-cyclone moving, So the cold weather of northern latitudes loss in lower latitudes North East of Iran, North West and Central parts of Iran. However, when Siberian high pressure combined with other patterns, its role in the advection of cold air have been considerable